‘LEX CALPURNIA DE PECUNIIS REPETUNDIS’ I JEJ ZNACZENIE DLA EWOLUCJI RZYMSKIEGO PRAWA KARNEGO - Kołodko, Piotr (Zeszyty Prawnicze, 2016)
THE LEX CALPURNIA DE PECUNIIS REPTETUNDIS AND ITS INFLUENCE ON THE EVOLUTION OF ROMAN CRIMINAL LAW Summary This paper concerns the contribution to Roman Criminal Law which has been undoubtedly done by lex Calpurnia de pecuniis repetundis. There is a possibility of presenting three aspects of the influence. The establishment of a first standing court (quaestio perpetua) should be perceived as a most outstanding achievement of the lex Calpurnia de pecuniis repetundis. In the later period (until Sulla dictatorship) quaestio perpetua de repetundis was treated as an example for the other standing courts and each of them were established by lex (or plebiscitum) to deal with one crime (or group of crimes). This solution has enabled a creation of a few standing courts which gradually deprived the Assemblies of the People (also concilia plebis) of competence concerning to penal practice. The other aspect of the influence concentrates on procedure that has been used during the trials in quaestio perpetua. It can be observed that the private law (ius civile) put emphasis on the character of the standing court established by lex Calpurnia. Quaestio perpetua did not have all features of criminal court (procedure legis actio sacramento in personam). On one hand it seems quite natural to take advantage of private law. There has not been any penal procedure that could have been adopted to the quaestio perpetua. Perhaps the civil procedure (legis actio sacramrnto in personam) was merely reasonable one for application in the standing court. On the other hand it cannot be rejected that the choice of legis actio sacramento in personam had to disable everyone without Roman citizenship to act as a plaintiff. It is worth remembering that the other standing courts had also something in common with private law (e.g. litis aestimantio mentioned in the lex Acilia repetundarum). The third possible influence on Roman criminal law can be seen in the character of provision of lex Calpurnia. It is beyond any doubts that the lex had provisions referring to procedure (above mentioned legis actio sacramento in personam), but it is not certain that there were a sanction (sanctio) which had a typical of penal character. The rogator established a sanctio as in simplum which proves that kind of sanction had not been commonly used in the Roman criminal law. It is very difficult to explain why such a santio had been put to the lex Calpurnia. One of the possibilities of solving this mystery regards the rogator as a weak person who was not able to enforce harsher penalty. It should be also taken into account that some objections may raise during the process of passing a law. The upper class of populus Romanus were not interested in establishing a harsher sanction. Having considered the overall arguments the lex Calpurnia de pecuniis repetundis had a great influence on the Roman criminal law. The first standing court (quaestio perpetua de repetundis) became an example for the other established later. The legal acts subsequent to lex Calpurnia had totally changed the Roman criminal policy where the preponderance of courts were the quaestiones perpeta